2004
DOI: 10.1167/iovs.04-0394
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Cone- and Rod-Induced Retinal Responsiveness in Macaque Retina by Optical Imaging

Abstract: The response topography in the retina, obtained by optical imaging, was consistent with psychophysical cone or rod sensitivity in humans and anatomic cone or rod distribution in humans and macaques. The cone- or rod-induced retinal responsiveness within the posterior pole region was noninvasively recorded within a short recording time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…Other functional imaging techniques of the retina include intrinsic optical imaging, 47 laser Doppler flowmetry, 42 laser speckle imaging, 48,49 and depth-resolved functional optical coherence tomography. 50,51 Intrinsic optical imaging measures reflectance associated with visual stimulation, albeit without laminar resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Other functional imaging techniques of the retina include intrinsic optical imaging, 47 laser Doppler flowmetry, 42 laser speckle imaging, 48,49 and depth-resolved functional optical coherence tomography. 50,51 Intrinsic optical imaging measures reflectance associated with visual stimulation, albeit without laminar resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic respiratory challenges with oxygen or carbogen modulate tissue oxygenation, as measured by oxygen polarographic electrodes (27). Visual stimulation modulates optical absorption and͞or scattering as detected by intrinsic optical imaging (3,34). Finally, visual-evoked BOLD fMRI of the retina (28) has been reported.…”
Section: Vascular Couplings and Bold Responsesmentioning
confidence: 99%
“…Changes in oxygen saturation have been measured in response to retinal stimulation using fundus reflectometry [95]. Other studies demonstrated changes in retinal reflectance in response to a flash stimulus that correlated with multifocal ERG [96]. While these fundus imaging techniques provide good spatial resolution in the transverse direction, they do not have depth resolving capability.…”
Section: Functional Retinal Imagingmentioning
confidence: 99%